2018
DOI: 10.1159/000494787
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation Thioredoxin Inhibits Advanced Glycation End Products-Induced Neurodegeneration

Abstract: Background/Aims: Diabetic retinopathy (DR) is one of the most serious complications of diabetes and is the leading cause of adult blindness in developed countries. Advanced glycation end products (AGEs) accumulation in diabetes is associated with its complications. Thioredoxin (Trx) is a small molecule (12kDa) antioxidant protein widely distributed in mammalian tissues, which has important biological functions including anti-apoptosis and transcriptional regulation. In a previous study, we found that Trx plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…This brought, as a consequence, a loss in anti-apoptotic and antioxidant function as well as a reduced cardiac protection function in a mice model of diabetic myocardial ischemia-reperfusion injury. It has also been shown that upregulation of thioredoxin is able to inhibit the expression of RAGE, suggesting crosstalk between RAGE and thioredoxin [93,94].…”
Section: Reactive Oxygen Species/reactive Nitrogen Species Are Intermmentioning
confidence: 99%
“…This brought, as a consequence, a loss in anti-apoptotic and antioxidant function as well as a reduced cardiac protection function in a mice model of diabetic myocardial ischemia-reperfusion injury. It has also been shown that upregulation of thioredoxin is able to inhibit the expression of RAGE, suggesting crosstalk between RAGE and thioredoxin [93,94].…”
Section: Reactive Oxygen Species/reactive Nitrogen Species Are Intermmentioning
confidence: 99%
“…Finally, among the nitrogen-containing group of phytochemicals, examples of potentially beneficial compounds in neurodegeneration/neurotoxicity here taken into account are sulforaphane (belonging to the glucosinolates group and found in cruciferous vegetables such as broccoli, cabbage, brussels sprouts, and cauliflower) [ 64 , 122 , 123 , 124 ] and spermine/spermidine (a polyamine found in soybean seeds) [ 68 , 125 , 126 , 127 ].…”
Section: An Overview Of Neuroprotective Phytochemical Classesmentioning
confidence: 99%
“…In the last decades, the search for an effective and potentially safe strategy to combat oxidative stress-mediated neuronal damage has increasingly prompted the investigation of naturally occurring compounds as antioxidant agents. The attenuation of oxidative stress by bioactive compounds belonging to different classes of phytochemicals including (i) flavonoids (quercetin, kaempferol and myricetin, scutellarin, baicalin, apigenin, catechins, epigallocatechin, and genistein) [ 52 , 61 , 81 , 82 , 83 , 88 , 94 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]; (ii) phenolic acids (syringic, gallic, caffeic, chlorogenic and salvianolic acids, and curcumin) [ 70 , 103 , 104 , 105 , 138 , 139 , 140 , 141 , 142 , 143 ]; (iii) flavonolignans (silymarin) [ 96 ]; (iv) stilbenes (resveratrol) [ 59 , 65 , 97 , 98 , 144 ]; (v) terpenes (bacosides/bacopasides, withanolides, and the carotenoids lutein and zeaxanthin) [ 7 , 110 , 113 , 115 , 145 , 146 , 147 ]; (vi) alkaloids (berberine and caffeine) [ 148 , 149 ]; (vii) glucosinolates (sulforaphane) and polyamines (spermine/spermidine) [ 123 , 124 ,…”
Section: Phytochemicals and Oxidative Stressmentioning
confidence: 99%
“…AGEs are well-known neurotoxins that form due to high glucose concentrations as seen in diabetes mellitus (DM) and can cause peripheral neuropathy, cognitive dysfunction, and retinal damage. [122863] In cultured peripheral neurons, SFN improves multiple parameters of AGE-induced neuronal damage, including the normalization of conduction velocity and blood flow. [28] In animal models of DM-induced neuropathy, pain behavior is lessened with SFN administration.…”
Section: Diabetes and Neuropathymentioning
confidence: 99%